Shelf-Life, Sensory Attributes and Microbiological and Chemical Characteristics of Processed Mirror Carp (Cyprinus carpio L.) Fillets - Patır, Bahri; Inanli, Ayse Gurel; Oksuztepe, Gulsum Ates; Dincoglu, A. Hulusi; Ilhak, O. Irfan (My University, 2009)
In the present study, fresh fillets of mirror carp, a type of carp common in Keban dam lake, were subjected to 10 or 15% salt (NaCl) followed by 0% (control), 1 or 5% potassium sorbate (w v(-1)) treatments prior to vacuum-packaged storage at 4 degrees C. The samples were analyzed during processing steps and on days 7, 14, 28, 42, 56, 70 and 84. Numbers of total aerobic mesophilic, psycrophilic bacteria, anaerobe bacteria, coliforms, Staphylococcus-Micrococcus, Lactobacillus, yeast and mold were found lower in the samples in 15%-salted and 5% potassium sorbate-treated group. Mold numbers reached to the highest level (4.83-7.49 log(10) cfu g(-1)) on day 28 of storage followed by a consistent decrease during the remaining days and dropped below detection limit (<1.00 log(10) cfu g(-1)) on 56-84 days. The differences in mold and yeast numbers between the 10% salted and 15% salted groups were found significant (p<0.05). pH reached to the highest level on days 14-28 of storage. Moisture level decreased to the minimum level on 56 day. Salt and a(w) levels were different (p<0.01) between salt groups. The levels of TVB-N and TBA constantly increased during storage. Sorbic acid level was determined in all groups between 102.14-593.19 mg/1000 g. Results of the present study revealed that the shelf life of the products was extended up to 2 months, overall acceptability of the products treated with potassium sorbate was higher and level of sorbic acid residues in the products did not posses a health treat.
Makale - Bilimsel Dergi Makalesi - Çok Yazarlı
Keywords: Mirror carp Salted fish Potassium sorbate Storage Quality